Low-cost dopant-free carbazole enamine hole-transporting materials for thermally stable perovskite solar cells - Zhou, S; Daskeviciene, M; Steponaitis, M; Bubniene, G; Jankauskas, V; Schutt, K; Holzhey, P; Marshall, AR; Caprioglio, P; Christoforo, G; Ball, JM; Malinauskas, T; et al. (Wiley, 2021)
Perovskite solar cells deliver high efficiencies, but are often made from high-cost bespoke chemicals, such as the archetypical hole-conductor, 2,2′,7,7′-tetrakis(N,N-di-p-methoxy-phenylamine)-9-9′-spirobifluorene (spiro-OMeTAD). Herein, new charge-transporting carbazole-based enamine molecules are reported. The new hole conductors do not require chemical oxidation to reach high power conversion efficiencies (PCEs) when employed in n-type-intrinsic-p-type perovskite solar cells; thus, reducing the risk of moisture degrading the perovskite layer through the hydrophilicity of oxidizing additives that are typically used with conventional hole conductors. Devices made with these new undoped carbazole-based enamines achieve comparable PCEs to those employing doped spiro-OMeTAD, and greatly enhanced stability under 85 °C thermal aging; maintaining 83% of their peak efficiency after 1000 h, compared with spiro-OMeTAD-based devices that degrade to 26% of the peak PCE within 24 h. Furthermore, the carbazole-based enamines can be synthesized without the use of organometallic catalysts and complicated purification techniques, lowering the material cost by one order of magnitude compared with spiro-OMeTAD. As a result, we calculate that the overall manufacturing costs of future photovoltaic (PV) modules are reduced, making the levelized cost of electricity competitive with silicon PV modules.